Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-01-09T19:03:09+01:00
A)
3x-2y=5
2x-y=4 /*(-2)

3x-2y=5
-4x+2y=-8

3x-4x=5-8

-x=-3 /*(-1)

x=3

3x-2y=5

3x-5=2y

3*3-5=2y

9-5=2y

4=2y /:2

2=y

x=3
y=2

spr.

3x-2y=5
2x-y=4

3*3-2*2=5
2*3-2=4

9-4=5
6-3=4

5=5
4=4


___________________________________________________

b)

2x+9y=-9
-3x+3y=8/*3

2x+9y=-9
-9x+9y=24

11x=-33
2x+9y=-9

x=-3
2*(-3)+9y=-9

x=-3
9y=-9+6

x=3
9y=-3/÷9

x=-3
y=-⅓




2010-01-09T20:10:54+01:00
A)
3x-2y=5
2x-y=4

3x-2y=5
y=2x-4

3x-2(2x-4)=5
y=2x-4

3x-4x+8=5
y=2x-4

x=3
y=2*3-4

x=3
y=2